Adaptasi Media Sosial oleh Organisasi Keagamaan di Indonesia: Studi Kanal YouTube Nahdlatul Ulama, NU Channel - Paelani Setia; Asep Muhamad Iqbal (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
This article discusses how religious organizations use social media by focusing its analysis on Nahdlatul Ulama and its YouTube channel, NU Channel. Using a qualitative method, this study collected its required data through online observation of NU Channel. This article argues that the assumption that Nahdlatul Ulama is a religious organization that tends to be traditionalist and conservative towards technological developments is incorrect. Nahdlatul Ulama is willing to adopt the internet as a new medium for conveying its religious views. The findings show that Nahdlatul Ulama is adaptive to social media as seen its adoption of YouTube as a new medium of religious studies conducted online on NU Channel. All this show a digital transformation within Nahdlatul Ulama’ religious studies, which is traditionally identical with pesantren, direct learning method with kiai, and other conventional ways of education and learning.